Fontes de zinco e fibra dietética em rações de leitões desmamados: desempenho e saúde intestinal - Fernandes, Carolina Dias (2016)
Additives are an important alternative for improving intestinal health of piglets. This study aimed to assess the impact of zinc oxide and encapsulated zinc, associated or not with dietary fiber on performance and intestinal health of piglets in nursery phase. The experiment was conducted at the Animal Science Department of the Federal University of Lavras. In the experiment it was used 140 barrows weaned at 21 days, with a weight of 5.32 ± 1.31 kg, housed in daycare facilities and divided into 35 bays with four animals. The experimental design was in randomized blocks, with five treatments: 1) Negative control supplemented with 139 ppm ZnO (72% Zn) (CN); 2) basal diet with ZnO (72% Zn) supplemented with 2500 ppm from 21 to 35 days and 1500 ppm from 36 to 63 days (OZ); 3) Basal feed with ZnO (72% Zn) and dietary fiber, supplemented with 2500 ppm ZnO and 8000 ppm dietary fiber from 21 to 35 days, 1500 ppm ZnO and 6000 ppm dietary fiber from 36 to 49 and 1500 ppm ZnO from 50 to 63 days (OZ + F); 4) basal diet supplemented with 800 ppm encapsulated Zn from 21 to 35 days and 500 ppm encapsulated Zn from 36 to 63 days (ZE); 5) basal diet supplemented with 8000 ppm dietary fiber and 800 ppm encapsulated Zn from 21 to 35 days, 6000 ppm dietary fiber and 500 ppm encapsulated Zn the 36 to 49 days and 500 ppm encapsulated Zn from 50 to 63 days (ZE + F), and seven repetitions with the bays as experimental plots. In the sixth and seventh day of the experiment, all animals were challenged with E. coli K88+ (1 mL, 106 CFU/mL for each day). The animals were weighed at the beginning and at 6, 14, 21, 28 and 42 days of experiment to assess the performance and once a day there was the evaluation of fecal score to determine the incidence of diarrhea. One animal per experimental unit was slaughtered at fourteen days after inoculation to evaluate the production of volatile fatty acids, microbial population, intestinal morphology and digestibility. The performance analysis showed lower consumption of the animals in the ZE treatment at 6 days (P <0.05). Regarding the incidence of diarrhea, the OZ treatment had a lower rate when compared to the ZE treatment. It was not found effect of treatments in the other variables of performance. The results of microbiological analysis of volatile fatty acids and histology were not affected by treatments. Thus, the zinc oxide 72% is effective in the control of post-weaning diarrhea, unlike the encapsulated zinc, which only provides a good performance of the animals when associated with dietary fibers.